Analyzing blast fragment projection effect of Feyzin domino accident - Jamel, Muhammad Aiman (2018)
This research is conducted in order to study the blast fragment projection effect of Feyzin domino accident and also to study the relationship between the probability for the domino accident to occur against the blast fragment projection distances. The method that is used for this research in order to achieved the objectives is the monte carlo simulation method. The result of the relationship between the probability for the domino accident to occur against the blast fragment projection is then tabulated into the graphically data. For the probabilistic analysis, both of the graph that has been made shown that the relationship between the probability of the domino accident to occur against the blast fragment projections distances were decrease monotonically. It can be justify that the longer the distances for the blast fragment projection effect to get the impact, the lower the probability for the domino accident to happened.